Faktor – Faktor yang Berhubungan Dengan Timbulnya Acne Vulgaris Pada Mahasiswi Angkatan 2021 Fakultas Kedokteran Universitas Batam - Thamrin Aziz; Suryanti Suryanti2; Wahyu Ramanda (Universitas Batam, 2022)
Background: Acne vulgaris is a chronic inflammation of the polysebasea follicles characterized by blackheads, papules, pustul, nodes and cysts. Acne vulgaris incidence in men is 42.5% and 50.9% in women settling into their 20s. Some factors acne vulgaris namely hormones, food, cosmetics, stress and sleep patterns. Methods: The study uses research design with observational analytical methods with a cross sectional approach. This research was conducted at the Campus of the Faculty of Medicine, Batam University in November 2021. Sampling technique uses a total sampling of 74 female students. Used univariate data analysis and bivariate analysis with the Chi-Square Test. Results: Respondents who suffered from acne vulgaris with abnormal menstrual cycles by 40.5%, patients with food had an effect of 52.7%, patients with cosmetics had an effect of 41.9%, patients with moderate to very severe stress by 70.3%, patients with poor facial cleaning habits by 31.1%, and patients with poor sleep patterns by 54.1%. Conclusion: The incidence of acne vulgaris in students in the class of 2021, Faculty of Medicine, Batam University, is 59.5%. There is no meaningful relationship between the menstrual cycle and acne vulgaris obtained values P-value 0.143 (>0.05) and there is a meaningful relationship between food risk factors (p-value = 0.004), cosmetics (p-value = 0.002), stress (p-value = 0.016), habits of cleaning the face (p-value = 0.001), sleep patterns (p-value = 0.00) with acne vulgaris